Exploring adaptive capacity at the land-sea interface: insights from coastal rural communities in Chile - Matías Barceló; Anna J Woodhead; Stefan Gelcich (Ecology and Society)
Coastal communities face increasing threats as global change diminishes the productivity of fisheries and agricultural land at the land-sea interface. Building adaptive capacities is essential to address threats to coastal livelihoods. Several theoretical frameworks exist to conceptualize and operationalize adaptive capacity that consider various domains and indicators. Local knowledge, as one of these domains, has been recognized as potentially crucial in determining adaptive capacity as it has been shown to contribute to risk reduction, climate change adaptation, and resilient food systems. However, little research has been conducted on indicators of adaptive capacity that include local knowledge for communities living at the land-sea interface. This study aims to assess how a measure of adaptive capacity, which includes indicators of local knowledge, connect to differences in fishers’ responses to real past and hypothetical declines in marine resources. To do this we conducted 99 semi-structured interviews in six communities along the coast of Southern Chile. Our findings reveal a high level of heterogeneity in the adaptive capacity of fishers, showing three types of individuals who displayed differential indicators of adaptive capacity. Fishers exhibited varied responses to income declines from marine resources, with 50% continuing to fish after a historic past decline, and 57.2% of fishers indicating they would also continue fishing in the event of a hypothetical 20% decline. However, a substantial 50% of decline in marine resources may lead to diversification away from fishing activities. Furthermore, our results illustrate how local knowledge, encompassing knowledge of land species and diversity of values, not only could strengthen and enable the ability to respond effectively in severe scenarios of decline that may drive diversification toward land-based activities, but also acts as a catalyst for other indicators of adaptive capacity, thereby promoting resilience and sustainable practices in the face of challenges. Thus, incorporating local knowledge in adaptive capacity frameworks is essential for supporting the well-being and adaptive strategies of coastal communities.